Angiogenesis outcomes of metformin utilization in diabetes mellitus: a systematic review and meta-analysis - Primasitha Maharani Harsoyo; Hanestya Oky Hermawan; Arisvia Sukma Hariftyani; Farah Aisha Shabrina; Anisya Dinda Paramitha; Saskia Ratna Desita; Yudi Her Oktaviono (Journal of the Pakistan Medical Association, 2024)
Objective: To review relevant literature regarding the role of metformin in angiogenesis among diabetic patients. Method: The systematic review and meta-analysis conducted from May to September 2022, and comprised search on Medline, ScienceDirect, ProQuest, Web of Science, EBSCOhost and Cochrane Library databases. The studies included were published in the English language and were human studies having angiogenesis endothelial markers as the outcomes of interest among patients of type 2 diabetes mellitus undergoing metformin therapy. Endothelial markers, including vascular endothelial growth factor, von-Willebrand-factor, plasminogen activator inhibitor-1, soluble vascular adhesion molecule- 1, intercellular adhesion molecule-1, soluble endothelialselectin, tissue plasminogen activator, urinary albumin excretion, platelet endothelial cell adhesion molecule-1 and thrombin-activatable fibrinolysis inhibitor, were assessed as angiogenesis outcomes. Data was statistically analysed using Review Manager 5.4. Results: Of the 413 studies identified, 8(1.9%) were included; 5(62.5%) randomised control trials, 2(25.0%) cross-sectional, and 1(12.5%) cohort studies, with overall 1199 patients. Among the outcomes, von-Willebrandfactor (p=0.01), soluble vascular adhesion molecule-1 (p<0.00001), intercellular adhesion molecule-1 (p=0.0003), soluble endothelial-selectin (p=0.007), and tissue plasminogen activator (p<0.00001) showed significantly lower levels after metformin treatment using the random effect methods. Conclusion: Metformin was found to have an additional effect of endothelial function improvement. Key Words: Platelet, Adhesion molecule, Endothelial cells, Plasminogen tissue, Dilatation, Fibrinolysis, Inflammation, Albumins, Diabetes mellitus.